Effects of Pre-Synchronization With Prostaglandin F2α and a Progestin, and Delayed Insemination on Pregnancy Rates With Sexed Semen in Replacement Beef Heifers - Oosthuizen, Nicola; Porter, Kristina; Burato, Samir; Goncalves, Lucas M.; Pohler, Ky G.; Fontes, Pedro L. P.; Lamb, G. Cliff (Frontiers in Animal Science, 2022)
To determine the effects of pre-synchronization and delayed fixed-time artificial insemination (TAI) on pregnancy rates (PR/AI) with sexed semen, 1,844 beef heifers were enrolled in a completely randomized design at 12 locations. Within a location, the heifers were randomly assigned to one of the five treatments: (1 and 2), heifers were administered prostaglandin F2α (PGF) on Day -7, gonadotropin-releasing hormone (GnRH), and a controlled internal drug releasing (CIDR) insert on Day 0, PGF at CIDR removal on Day 7, and a second injection of GnRH at TAI 72 h later with either conventional (CTRL72-CNV) or sexed semen (CTRL72-SEX); (3 and 4), treated the same as CTRL72 but received a CIDR insert on Day -7 at PGF administration and TAI at 60 h with either conventional (CIDR60-CNV) or sexed semen (CIDR60-SEX); (5), treated the same as CIDR60 but had TAI delayed to 72 h with sexed semen (CIDR72-SEX). Estrus detection patches were applied to all heifers on Day 7 and were evaluated for activation at TAI. Estrus expression did not differ (p = 0.92) between CIDR60 and CIDR72 heifers, but was greater (p < 0.001) in CIDR60 and CIDR72 heifers compared with CTRL72 heifers. Among treatments, PR/AI differed (p < 0.001) and were greater (p ≤ 0.003) in CTRL72-CNV and CIDR60-CNV heifers than CIDR60-SEX and CIDR72-SEX heifers (51.6 and 48.1 vs. 37.5 and 25.3%, respectively). In addition, PR/AI were greater (p < 0.001) in CTRL72-SEX and CIDR60-SEX heifers when compared with CIDR72-SEX (42.0 and 37.5 vs. 25.3%, respectively) heifers but only tended (p = 0.09) to differ between CTRL72-SEX and CIDR60-CNV heifers. No differences (p = 0.33) were determined between CTRL72-CNV and CIDR60-CNV or between CTRL72-SEX and CIDR60-SEX heifers (p = 0.22). In conclusion, no differences were determined between heifers pre-synchronized with only PGF and those pre-synchronized with PGF and a CIDR insert when inseminated with either conventional or sexed semen. Therefore, the use of a CIDR insert for an additional 7 days was not beneficial to PR/AI when heifers were TAI at 60 h with either conventional or sexed semen. Furthermore, delaying TAI to 72 h with sexed semen after pre-synchronization with both PGF and a CIDR insert had a negative impact on PR/AI.